Adenosquamous carcinoma in the biliary tract: association of the proliferative ability of the squamous component with its proportion and tumor progression. (3rd April 2017) - Hoshimoto, Sojun; Hoshi, Sayuri; Hishinuma, Shoichi; Tomikawa, Moriaki; Shirakawa, Hirofumi; Ozawa, Iwao; Wakamatsu, Saho; Hoshi, Nobuo; Hirabayashi, Kaoru; Ogata, Yoshiro
Abstract: Objectives: The purpose of this study was to evaluate the association of the proliferative ability of squamous cell carcinoma (SCC) component with its proportion and tumor progression in adenosquamous carcinoma (ASC) in the biliary tract. Methods: Nine patients with ASC in the biliary tract (four each in the gallbladder and the extrahepatic bile duct and one in the ampulla of Vater) who underwent surgical resection were retrospectively reviewed. Results: The proportion of the SCC component in the primary sites ranged from 30% to 95%. The Ki-67 index of the SCC component was higher than that of the adenocarcinoma component in all cases, regardless of the component ratio in the patients' primary lesions. Predominance of the SCC component in the advancing region of the tumor, in angiolymphatic invasion and in perineural invasion was observed in most of the cases. The component ratio in metastatic lymph nodes differed from that in the corresponding primary lesions in all six cases with lymph node metastasis. Among these cases, the proportion of the SCC component was increased in the metastatic lymph nodes compared with that in the corresponding primary lesion in two cases, whereas the proportion was decreased in four cases. Conclusions: The SCC component of ASC in the biliary tract displayed a relatively higher proliferative ability, which might be associated with local invasiveness. However, not only the high proliferative ability of the SCC component but also other biological factors might contribute to tumor progression and metastasis in ASC of the biliary tract.